ALK Protein Analysis by IHC Staining after Recent Regulatory Changes: A Comparison of Two Widely Used Approaches, Revision of the Literature, and a New Testing Algorithm. Issue 4 (April 2016) - Marchetti, Antonio; Di Lorito, Alessia; Pace, Maria Vittoria; Iezzi, Manuela; Felicioni, Lara; D'Antuono, Tommaso; Filice, Giampaolo; Guetti, Luigi; Mucilli, Felice; Buttitta, Fiamma
ABSTRACT : Introduction: : Recent regulatory changes have allowed the diagnostic use of immunohistochemical (IHC) analysis for the identification of patients with non–small cell lung cancer who are eligible for treatment with anaplastic lymphoma receptor tyrosine kinase (ALK) inhibitors. The U.S. Food and Drug Administration has approved the VENTANA ALK (D5F3) CDx Assay (Ventana Medical Systems, Tucson, AZ) as companion diagnostics, and the Italian Medicines Agency has recognized IHC analysis as a diagnostic test indicating an algorithm for patient selection. Methods: : On the basis of the new regulations, we compared two commonly used IHC assays on 1031 lung adenocarcinomas: the VENTANA ALK (D5F3) CDx Assay with the OptiView Amplification Kit (Ventana Medical Systems) and a standard IHC test with the clone 5A4 (Novocastra, Leica Biosystems, Newcastle Upon Tyne, United Kingdom) along with their interpretative algorithms. Fluorescence in situ hybridization (FISH) was performed in all cases. Next‐generation sequencing was performed in FISH/IHC analysis–discordant samples. Results: : FISH gave positive results in 33 (3.2%) cases. When FISH was used as a reference, the VENTANA ALK (D5F3) CDx assay had a sensitivity of 90.9% ± 2.6%, a specificity of 99.8% ± 0.6%, and positive and negative predictive values of 93.8% ± 2.1% and 99.7% ± 0.6%, respectively. The clone 5A4–based IHC test showed a sensitivity of 90.9% ± 2.6%, a specificity of 98.3% ± 1.3%, and positive and negative predictive values of 63.8% ± 4.2% and 99.7% ± 0.6%, respectively. Five cases with IHC analysis/FISH‐discordant results in our series were analyzed together with those previously reported in the literature. Overall, data from 35 patients indicate a response rate to ALK inhibitors in 100% of FISH‐negative/IHC analysis–positive cases (seven of seven) and 46% of FISH‐positive/IHC analysis–negative cases (13 of 28), respectively. Conclusions: : Our results confirm the difficulty in managing an IHC test without amplification in the absence of confirmatory FISH analysis, as well as the possibility of performing a direct diagnosis in approximately 90% of patients by the VENTANA ALK (D5F3) CDx Assay. On the basis of the recent regulatory changes, the data that have emerged from the literature, and the results of the present study, a new algorithm for ALK assessment in non–small cell lung cancer has been devised.